1999
DOI: 10.1046/j.1365-201x.1999.00480.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nitric oxide inhalation on pulmonary gas exchange during exercise in highly trained athletes

Abstract: The pathophysiology of exercise-induced hypoxaemia in elite athletes is still unclear but several studies indicate that a diffusion limitation, which could be explained by an interstitial pulmonary oedema, is a major contributing factor. Stress failure would induce a haemodynamical interstitial oedema with inflammatory reaction and release of mediators like histamine. Histamine release was found to be correlated with the hypoxaemia in elite athletes. If stress failure is involved, inhalation of pulmonary vasod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
1
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 33 publications
1
16
1
1
Order By: Relevance
“…As VA/Q mismatching contributes to EIH [15,38,48], it is tempting to suggest that low NO levels may favour EIH development. This is in accordance with Durand et al [10], who showed that exogenous NO may modify EIH in athletes during the last phase of an incremental test in normoxic conditions. By contrast, Sheel et al [40] failed to find any effect of NO inhalation on gas exchange during normoxic and hypoxic maximal exercises in the same population.…”
Section: No In Athletes With Eihsupporting
confidence: 88%
See 1 more Smart Citation
“…As VA/Q mismatching contributes to EIH [15,38,48], it is tempting to suggest that low NO levels may favour EIH development. This is in accordance with Durand et al [10], who showed that exogenous NO may modify EIH in athletes during the last phase of an incremental test in normoxic conditions. By contrast, Sheel et al [40] failed to find any effect of NO inhalation on gas exchange during normoxic and hypoxic maximal exercises in the same population.…”
Section: No In Athletes With Eihsupporting
confidence: 88%
“…During intense exercise, several previous studies have suggested that these athletes may experience VA/Q mismatch leading to pulmonary gas exchange impairment and hypoxaemia [38,48]. Durand et al [10] recently showed that inhaled NO may modify the drop in oxygen arterial partial pressure (PaO 2 ) suggesting that NO may be involved in EIH probably by modulating VA/Q homogeneity. Moreover, Duplain et al [9] recently pointed out that subjects with a low level of exhaled NO had higher pulmonary arterial pressure during exposure to hypoxia.…”
Section: Introductionmentioning
confidence: 98%
“…The improvement in V '/Q ' with inhaled L-NAME is a novel finding and accords with the results of VENEGAS et al [38], who found that inhaled NO (40 parts per million (ppm)) increased the spatial heterogeneity of V '/Q ' in supine dogs measured by positron emission tomography, although HOPKINS et al [39] found no V '/Q ' deterioration in anaesthetized dogs given 80 ppm NO. Deterioration in V '/Q ' matching with inhaled NO has also been shown in studies of patients with chronic obstructive pulmonary disease [40] and in normal humans [40,41]. Two recent studies found a trend towards better gas exchange with partial elimination or diversion of endogenous NO production.…”
Section: Differences Between Effects Of Nmentioning
confidence: 84%
“…The race time was faster and the expressed perceived exertion was lower with sodium bicarbonate than in response to saline exercise [median of 6 min 21 s (range 6 min 16 s to 6 min 58 s) vs. 6 min 28 s (6 min 23 s to 7 min 10 s) and median of 18 (range [13][14][15][16][17][18][19] vs. 19 (17)(18)(19), respectively; P Ͻ 0.05].…”
Section: Resultsmentioning
confidence: 99%
“…1,14,19,27,48,49) and also, in some athletes, as a reduced saturation of Hb (Sa O 2 ; Refs. 17,23,37,51). Insufficient increase in ventilation (14), a pulmonary diffusion limitation (14), and ventilation-perfusion inequality (21,26) may contribute to reduce Pa O 2 .…”
mentioning
confidence: 99%